THE EFFECT OF FUNDAMENTAL FACTORS, EARNING PER SHARE AND EXCHANGE RATE ON STOCK RETURNS WITH DIVIDEND POLICY AS INTERVENING VARIABELS - Agustina, Sri; Purnomo, Listiya Ike (Finance and Banking Program, Accounting Department, Politeknik Negeri Semarang, 2022)
The purpose of this study was to determine the effect of fundamental factors on earnings per share, exchange rate and dividend policy as intervening variables on stock returns. In this study, fundamental factors are measured using financial ratio. The higher the stock return, the higher the welfare of the shareholders. Increased stock returns will affect potential investors to invest in the company. This study uses a sample of banking companies indexed by infobank15 which are listed on the Indonesia Stock Exchange during the 2016-2020 period. The sampling technique used in this research is the purposive side method, the sample obtained is 9 banking companies indexed by infobank15, using the Eviews.12 analysis method. Based on the results of the study, it shows that the fundamental factors which are proxied by the debt to equity ratio (DER), the exchange rate have an effect on stock returns. While the fundamental factors that are proxied by return on assets, earnings per share and dividend policy have no effect on stock returns. The dividend policy variable is able to mediate the relationship between the fundamental factor variables which are proxied by return on assets and the exchange rate to stock returns. Meanwhile, the dividend policy variable is not able to mediate the relationship between the fundamental factor variables which are proxied by the DER and earnings per share to stock returns.